The influence of tropical basin interactions on the 2020–2022 double-dip La Niña - Hasan, Nahid A.; Chikamoto, Yoshimitsu; McPhaden, Michael J. (Frontiers in Climate, 2022)
The recharge oscillator mechanism suggests that a strong El Niño event can trigger a following La Niña event that sometimes lasts for two or even three years through warm water volume preconditioning within the tropical Pacific. However, a prominent and persistent “double-dip” La Niña event appeared in the boreal winters of 2020/21 and 2021/22 without any significant El Niño preconditioning. Here we explore the possibility that tropical basin interactions may have initiated and helped to prolong La Niña conditions over the two-year period 2020-22. This period was preceded by a strong positive Indian Ocean Dipole (IOD) during the boreal fall of 2019 that gave way to basin-scale warming in the Indian Ocean in early 2020 and a notable tropical Atlantic warming in the boreal winter of 2019/20. Later, a strong Atlantic Niño developed in the boreal summer of 2021. Using composite analyses to characterize earlier double-dip La Niñas, we argue the unusual sequence of events in 2019–2021 in the Indian and Atlantic Oceans may have energized and sustained the 2020–22 La Niña event without any significant warm water volume preconditioning within the tropical Pacific.